Study on suitability of Derawan Island as marine tourism destination towards development of sustainable tourism in the new capital city candidate of Indonesia. Issue 1 (October 2021) - Simarangkir, O R; Utami, P B; Ricky; Nani; Tawang, F; Irwan; Kodiran, T
Abstract: Derawan Island is one of the leading tourist destinations in Kalimantan Timur Province which is a candidate for the new capital city of Indonesia. Marine tourism on Derawan Island relies on the potential of marine resources so that a suitability study is needed for the development of sustainable tourism. This study aims to determine the suitability of marine tourism, especially the interest in diving and snorkeling in sites of Derawan Island. Data collection was carried out by surveying in December 2020 at five snorkeling and six popular dive sites in Derawan Island. Data on coral community, the number of coral fish species, and the water quality parameters are used to analyze the suitability of marine tourism. Line Intercept Transect (LIT) method was used to collecting coral community data, Underwater Visual Census (UVC) method was used to collect data on the abundance of reef fish species, and in situ water quality parameters. Tourism suitability index formula (IKW) using the four classification marine tourism suitability matrix was used to analyze the data. The results of the analysis show the suitability index for diving tourism as a whole is in suitable to very suitable category, while the snorkeling tourism suitability index is in the suitable category.